(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the role of modern technologies in the development of communicative competence in the educational process. The article examines the definition of communicative competence, its importance in education, and how it can be developed using modern technologies. Recommendations are given for teachers and educational institutions on improving students’ communicative skills through the use of modern technologies.